An assessment of the e-learning readiness of faculty and undergraduate students of the Institute of Library and Information Science - Nogoy, Lemuel Ramon M.; Carcellar, Marie Desiree R. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
E-learning is the convergence of internet technology, computer technology and learning. E-learning has shown its versatility having been implemented by organizations in various disciplines and having been used in numerous countries. It shifts the focus from the instructor to the student. Organizations and their members will enjoy a host of benefits by embracing e-learning. However, they must perform careful planning and they must address areas of concern to realize its full potential. In line with this, this study determined the readiness of the faculty and undergraduate students of the UP Institute of Library and Information Science for e-learning. The study gauged the respondents' readiness in terms of their attitudes and perceptions with regard to e-learning, their computer skills as well as the technology infrastructure available to them.
A total of 74 student respondents and 8 full-time faculty members participated in the study. The study focused on seven factors that would determine e-learning readiness, namely: organization strategy, content, training process, culture, financial, technology and skills. The student respondents' areas of concern were as follows: access to a slow internet connections, distractions outside the classroom setting that might hamper learning and, reservations regarding open courseware and materials from commercial providers.
Teacher respondents expressed concerns with their web programming skills as well as with their slow internet connection. They also worried that e-learning adds to their workload and that it was not one of the Institute's priorities. Other than those mentioned above, all the respondents had positive remarks overall.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Institute of Library and Information Science -- Faculty; University of the Philippines Institute of Library and Information Science -- Students; Information services -- User education -- Philippines